(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
In elementary school, working with all students in the classroom is more complex and challenging for the teacher. Although the teacher organized the lesson perfectly, there are students in the class who have a low level of mastery. This article discusses ways to work with students with learning disabilities.